Modeling and simulation of a rollerball microfluidic device - Rojas-Solorzano, L.; Shelley L., Anna; Bradeddine, Bourtal; Amon, Cristina H. (ASME, 2009)
The fluid delivery process through a rollerball device is investigated by means of physical modeling and numerical simulations. The microfluidic device is intended to deliver liquid above a substrate interacting with the surrounding air. While the fluid is delivered, air entrainment occurs through the capillary gap, creating a two-phase liquid-gas mixture whose composition and properties affect significantly the quality of the continuous fluid deposition. For the numerical solution of the 2D two-phase flow governing equations, the finite volumebased finite element method is used with 2nd order time-space schemes for the fully coupled system of equations. The quality of the liquid micro-volume delivery proves to be largely affected by both the speed of the roller and fluid properties. It is found that only under very low speed and some fluid properties, it is possible to guarantee a gas free liquid deposition. Envisioning the potential use of this convenient and popular device in the deployment of microfluid layers or substances at very small quantities with controlled quality, it is apparent the need for handling and channeling out the air entrainment without perturbing the liquid quality
Keywords: Research Subject Categories::TECHNOLOGY::Engineering mechanics; mechanical engineering